Effects of Computer-Mediated Instruction (Cmi) on Student-Teachers’ Misconceptions and Achievement in Physics - Onyukwu Chima Onyedineke; Mangut Mankilik (Journal of Higher Education and Academic Advancement, 2024)
Physics is one of the natural sciences taught in Colleges of Education in Nigeria as a teaching subject with course units in line with the branches of physics, such as mechanics, thermodynamics, electromagnetism, optics, acoustics, astronomy and electronics. These course units are generally taught using the traditional lecture approach which neither give students opportunity to participate actively in the learning process nor co-construct knowledge as required in a science classroom. Consequently, students struggle with misconceptions which lead to poor academic achievement in physics. This study investigated the effects of computer-mediated instruction (CMI) on physics student-teachers’ misconceptions and achievement in Federal Colleges of Education, South-South Zone, Nigeria. The study adopted pretest-posttest one control group quasi-experimental design with intact classes. The study population comprised 51 physics student-teachers from the three federal colleges of education in the South-South zone of Nigeria who registered for Mechanics and Properties of Matter II during the 2018/2019 academic session. Simple random sampling technique was use to select the two federal colleges of education that participated in the study. Data were collected using Mechanics and Properties of Matter Misconceptions and Achievement Test (MPMMAT). Descriptive and inferential statistics were used for analysis with the assistance of Statistical Package for Social Sciences (SPSS) version 23.0 software. Result findings showed that Physics students hold a number of misconceptions on Mechanics and Properties of Matter II. Results equally revealed that CMI can improve students’ achievement in Mechanics and Properties of Matter II and can also reduce their misconceptions in the course. The study concluded that computer-mediated instruction (CMI) is an effective teaching approach which can reduce physics student-teachers’ misconceptions in mechanics and improve their academic achievement.